Mybl2 rejuvenates heart explant‐derived cells from aged donors after myocardial infarction - Rafatian, Ghazaleh (Aging Cell, 2020)
While cell therapy is emerging as a promising option for patients with ischemic cardiomyopathy (ICM), the influence of advanced donor age and a history of ischemic injury on the reparative performance of these cells are not well defined. As such, intrinsic changes that result from advanced donor age and ischemia are explored in hopes of identifying a molecular candidate capable of restoring the lost reparative potency of heart explant‐derived cells (EDCs) used in cell therapy. EDCs were cultured from myocardial biopsies obtained from young or old mice 4 weeks after randomization to experimental myocardial infarction or no intervention. Advanced donor age reduces cell yield while increasing cell senescence and the secretion of senescence‐associated cytokines. A history of ischemic injury magnifies these effects as cells are more senescent and have lower antioxidant reserves. Consistent with these effects, intramyocardial injection of EDCs from aged ischemic donors provided less cell‐mediated cardiac repair. A transcriptome comparison of ICM EDCs shows aging modifies many of the pathways responsible for effective cell cycle control and DNA damage/repair. Over‐expression of the barely explored antisenescent transcription factor, Mybl2, in EDCs from aged ICM donors reduces cell senescence while conferring salutary effects on antioxidant activity and paracrine production. In vivo, we observed an increase in cell retention and vasculogenesis after treatment with Mybl2‐over‐expressing EDCs which improved heart function in infarcted recipient hearts. In conclusion, Mybl2 over‐expression rejuvenates senescent EDCs sourced from aged ICM donors to confer cell‐mediated effects comparable to cells from young nonischemic donors.